Implementation Of Government Procurement Of Goods/Services For Print And Duplication Expenditure Through E-Catalogue In South Bengkulu Regency - Bambang Irawan; Karona Cahya Susena; Dodi Hardinata (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Changes in the mechanism for procuring government goods / services, which have been carried out through tenders and conventional procurement, have become online (online) in the e-catalogue system in accordance with LKPP (Government Goods / Services Procurement Policy Agency) regulation Number 9 of 2021 concerning Online Stores and Electronic Catalogues in Government Goods / Services Procurement. In this case, to implement the provisions of article 72 paragraph (5) and article 72 A paragraph (3) of Presidential Regulation Number 12 of 2021 concerning Amendments to Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods / Services. Demanding business actors or goods/services providers to onboard their businesses to the e-catalogue system. The research methodology uses a descriptive qualitative approach, to find out the extent to which business actors' responses to e-catalogue implementation affect business sustainability. To obtain the natural conditions of the object of research, this research uses data collection methods through interviews, field observations and documents